A new promising «Niyat» variety of cotton created at Khorezm Mamun Academy - F.Q.Jumaniyazov; G.R.Qadamova (Zien Journals, 2022)
This article provides information on the valuable economic characteristics of the new and promising «Niyat» variety of cotton, which is quick-ripening, fertile, resistant to diseases and pests, able to adapt to various extreme conditions, gives type IV and V fiber, suitable for the soil-climatic conditions of Khorezm region.
Keywords: New; promising cotton varieties; soil-climate conditions of Khorezm region